2018
DOI: 10.1371/journal.pone.0195440
|View full text |Cite
|
Sign up to set email alerts
|

Global trends of local ecological knowledge and future implications

Abstract: Local and indigenous knowledge is being transformed globally, particularly being eroded when pertaining to ecology. In many parts of the world, rural and indigenous communities are facing tremendous cultural, economic and environmental changes, which contribute to weaken their local knowledge base. In the face of profound and ongoing environmental changes, both cultural and biological diversity are likely to be severely impacted as well as local resilience capacities from this loss. In this global literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(208 citation statements)
references
References 96 publications
5
151
3
6
Order By: Relevance
“…However, with the addition of tribal boundary data, we show that decreasing suitability for Kuta in Northland is likely to inhibit local Kuta availability and continued use of harvest sites that have been treasured for generations, particularly Lake Ngātu. Reduced local access to species is typically accompanied by a loss of biocultural knowledge (Aswani, Lemahieu, & Sauer, ; Hanazaki, Herbst, Marques, & Vandebroek, ; Soga & Gaston, ). Using traditional Kuta harvest sites remains important for cultural identity and direct ancestral connections to the environment (Harmsworth & Awatere, ; Kapa, ; Kawharu, ; Roberts et al., ), especially in the northern and central regions of New Zealand's North Island (Kapa, ; Wehi, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, with the addition of tribal boundary data, we show that decreasing suitability for Kuta in Northland is likely to inhibit local Kuta availability and continued use of harvest sites that have been treasured for generations, particularly Lake Ngātu. Reduced local access to species is typically accompanied by a loss of biocultural knowledge (Aswani, Lemahieu, & Sauer, ; Hanazaki, Herbst, Marques, & Vandebroek, ; Soga & Gaston, ). Using traditional Kuta harvest sites remains important for cultural identity and direct ancestral connections to the environment (Harmsworth & Awatere, ; Kapa, ; Kawharu, ; Roberts et al., ), especially in the northern and central regions of New Zealand's North Island (Kapa, ; Wehi, ).…”
Section: Discussionmentioning
confidence: 99%
“…Place-based knowledge, as practiced by pastoralists and ranchers, shapes their identities, families, communities, and their ecological environments (Knapp and Fernández-Giménez 2009;Fernández-Giménez 2015;and Dong et al 2016). Research interpreting rancher local knowledge is limited (Knapp and Fernández-Giménez 2009), yet research on local ecological knowledge in natural resources management generally suggests such place-based knowledge shapes and is shaped by emotional, religious, spiritual, social connections to and management of specific places (Masterson et al 2017;Plumwood 2006;Fernández-Giménez 2015;and Fernández-Giménez and Estaque 2012;Robinson et al 2000;Aswani et al 2018). Ranchers' local knowledge may also exist at scales that are different from those of research-derived knowledge and practice (Cote and Nightingale 2012).…”
Section: Fostering Hope and Sense Of Place In Range Decision-makingmentioning
confidence: 99%
“…Thus, there is regular exchange of information between locally situated knowledge and the larger domain of science, as both complement each other. Even so, the scope to enhance linkages between LEK and formal science might be lost or be rendered irrelevant in changing fisheries and fisher communities experiencing rapid hydrological and climate change (Drew & Henne, ; Gómez‐Baggethun & Reyes‐Garcia, ; Aswani, Lemahieu, & Sauer, ). Degradation and transformation of LEK are also likely to negatively affect biodiversity conservation and sustainable fisheries efforts involving local communities (Aswani et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Degradation and transformation of LEK are also likely to negatively affect biodiversity conservation and sustainable fisheries efforts involving local communities (Aswani et al, 2018). Berkes et al (2000) showed that LEK comes about through long-sustained iterations of trial-and-error and learning practices that converge upon principles of adaptive resource management.…”
mentioning
confidence: 99%